Rectal Pouch Index: A Prognostic Indicator for Constipation after Surgery for High and Intermediate Anorectal Malformations - Sharma, Nitin; Pratap, Akshay; Bajpai, Minu (European Journal of Pediatric Surgery, 2014)
Background and Introduction Constipation following posterior sagittal anorectoplasty (PSARP) is common. We correlated the dimensions of rectal pouch before PSARP with the postoperative bowel habit. Classical PSARP was modified with tapering of rectal pouch by plication of its walls thus preserving the internal sphincter because we believe that this preserves continence and lead to better results. It was observed that a distinct relationship exists between the preoperative size of the rectal pouch and constipation.Aim The aim of this study is to correlate the dimensions of preoperative rectal pouch with postoperative constipation.Materials and Methods PSARP was performed (n: 45) in anorectal malformations using an indigenous muscle stimulator. Before PSARP, a distal cologram via high sigmoid colostomy was performed. All the distal cologram were performed by a single senior radiologist and the pressure was kept constant between 15 and 20 cm of water while filling to rule out the confounding factor related to incomplete filling. Rectum index was calculated as follows: The maximum radiological diameter of the rectum within the pelvis in the sagittal plane was multiplied by the maximum diameter of the rectum in the frontal plane. The result of this calculation was divided by the product of multiplying the distance between the ischial spines and the distance between the posterior surface of the pubic symphysis and the anterior surface of the last sacral vertebrae.Results Symptomatic constipation requiring treatment developed in 25 patients (48%). None of these patients had anal stenosis or stricture. Constipation was managed by dietary measures and laxatives. Fifteen patients (60%) had grade 1 constipation and responded favorably. Eight and two patients had grades 2 and 3 constipation, respectively. Those patients who had a rectal pouch index of less than 0.8 had mild constipation grades 0 and 1, whereas those in whom the rectal pouch index was more than 0.8 had severe degrees of constipation (grades 2 and 3).Conclusion Measuring the rectal pouch index can help in identifying the group which is likely to develop constipation after PSARP. These patients can be put on bowel training early on, after the colostomy closure, instead of waiting.
Keywords: rectal pouch index; constipation; PSARP; rectal placation; ARM